Disclose or Not Disclose? An Investigation into The Relationship between ‎Corporate Governance Mechanisms and Impression Management in The ‎Sustainability Reporting - Bojan, Andreea Madalina (International Journal of Accounting and Economics Studies, 2025)
The main purpose of this research is to examine the relationship between corporate ‎governance mechanisms, in terms of specific governance scores, and the tendency to use ‎impression management techniques in sustainability reporting, measured by several aspects, ‎such as the level of optimism, positive words, and negative words. This analysis includes ‎several control variables to observe the influence at the company level. The research hypotheses ‎are tested using a sample consisting of companies from Eastern European geographical areas ‎and non-financial industries. The time frame analyzed is the period between 2022 and 2023, ‎and regression models estimated for panel data using random-effects are applied. The ‎findings draw a clear picture of the impact exerted by corporate governance mechanisms on ‎impression management, demonstrating that governance, management, and shareholders' ‎scores have a positive influence on the level of optimism, while positive and negative words ‎exposed in sustainability reporting are significantly influenced by management and CSR ‎strategy scores. Results summary may have implications for business and academic ‎environments. Thus, company representatives could be interested in what corporate ‎governance practices may be applied to avoid and anticipate the impression ‎management tendency, while for academics, this study represents a valuable resource in terms of present ‎and future research‎.
Keywords: Corporate Governance; Impression Management; Textual Characteristics; Non-financial ‎Disclosure; Sustainability Reporting